k! * (k + 1) == (k + 1)!; How?  TOPIC_SOLVED

Complex numbers, rational functions, logarithms, sequences and series, matrix operations, etc.

k! * (k + 1) == (k + 1)!; How?

Postby syntaxerror on Wed Jul 24, 2013 6:03 pm

k!(k + 1) = (k + 1)!

How does the left simplify to the expression on the right?

(I understand what factorial is, and I can find rules for multiplying two factorials, but I don't have any rules for multiplying a sum by a factorial.)
syntaxerror
 
Posts: 1
Joined: Wed Jul 24, 2013 6:00 pm

Sponsor

Sponsor
 

Re: k! * (k + 1) == (k + 1)!; How?  TOPIC_SOLVED

Postby jg.allinsymbols on Thu Jul 25, 2013 2:31 am

syntaxerror wrote:k!(k + 1) = (k + 1)!

How does the left simplify to the expression on the right?

(I understand what factorial is, and I can find rules for multiplying two factorials, but I don't have any rules for multiplying a sum by a factorial.)


k!(k+1)=(k+1)*k!
=(k+1)*(k)(k-1)(k-2)...(3)(2)(1)
=(k+1)!


Look carefully that k=(k+1)-1
jg.allinsymbols
 
Posts: 71
Joined: Sat Dec 29, 2012 2:42 am


Return to Advanced Algebra ("pre-calculus")